Réponses

2013-07-24T15:34:07+02:00

Exercice 57
----------------

 

E  =  −4(x + 3) + 5(6 + x)
    =  −4x − 12 + 30 + 5x
    =  x + 18

 

F  =  (8 + 2x) × 3 + 7(3x + 7)

    =  24 + 6x + 21x + 49
    =  27x + 73

 

G  =  4x(−2x + 3) + 2x(3x − 6)
     =  −8x² + 12x + 6x² − 12x
     =  −2x²

 

H  =  5x(6 − 7x) − x(8 + 2x)
     =  30x − 35x² − 8x − 2x²
     =  −37x² + 22x

 

 

 

Exercice 58
----------------

 

I  =  6x(3x + 4) + 4(5x + 3)
   =  18x² + 24x + 20x + 12
   =  18x² + 44x + 12

 

J  =  −3x(−2x + 6) + x(4x − 2)
    =  6x² − 18x + 4x² − 2x
    =  10x² − 20x

 

K  =  −4(6 + 5x) + 9x(2x − 3)
     =  −24 + 20x + 18x² − 27x
     =  18x² − 7x − 24

 

L  =  7x(3x − 2) − x(−6 + x)
    =  21x² − 14x + 6x − x²
    =  20x² − 8x